Flood 2.0: Facebook use and reactions during the 2011/2012 flood in Thailand - Panom Gunawong (2018)
Copyright © 2015 Inderscience Enterprises Ltd. This paper explored the use and reactions of Thaiflood Facebook during the major 2011/2012 flood in Thailand. The Facebook page was used mostly for providing situation update data. This type of message drew more reactions ('Like', 'Comment', and 'Share') than those from other types such as flood response and opinion sharing. Interestingly, it was also seen that requests were made by Facebook users. These findings are of crucial importance to the organisations concerned with disaster management, as these insights will help them to improve provision of useful information for people affected by floods and also address their needs effectively.